Polymer aggregation control in polymer–fullerene bulk heterojunctions adapted from solution. Issue 1 (18th November 2014) - Kästner, Christian; Egbe, Daniel A. M.; Hoppe, Harald
Abstract : In a semi-quantitative approach, we unified the inter-chain and intra-chain polymer order into a single parameter of combined structural order P CSO . Relating all photovoltaic parameters to the P CSO, we find convincing evidence, that polymer aggregation supports charge extraction, reduces photocurrent generation and slightly reduces photovoltage. Abstract : It is common knowledge that the polymer conformation and its phase separation with fullerene derivatives are delicate issues crucially impacting on the photovoltaic parameters of polymer based solar cells. While strongly intermixed polymer–fullerene phases presumably provide a large interfacial area and consequently a high quantum efficiency of exciton dissociation, pristine and primarily ordered polymer and fullerene domains may support efficient charge transport and its percolation. To study the aggregation and phase separation behaviour in polymer solar cells we investigated the counterbalancing influences of the polymer solution concentration and its blending ratio with PCBM ([6, 6]-phenyl-C61 -butyric acid methyl ester) on the basis of a semi-crystalline anthracene-containing poly( p -phenylene-ethynylene)- alt -poly( p -phenylene-vinylene) (PPE-PPV) copolymer statistically bearing branched 2-ethylhexyloxy and linear octyloxy side-chains (AnE-PV stat ). The polymer aggregation was semi-quantitatively evaluated on the basis of its optical fingerprints and varied with both, the solution and the PCBM concentration, yielding a specific maximum within the parameter range studied. Upon relating photovoltaic parameters to the order within the polymer phase, the counterbalancing effect between charge generation and transport for increasing polymer aggregation is demonstrated, in agreement with sound hypotheses.